Reconceptualizing School Discipline Policy: Restorative-Educational Religious Sanctions within an Islamic Character Ecosystem - Edi Purwanto; Hidayah Uswatun Kasanah; Ervin Alberthina; Deny Hadi Siswanto (Jurnal Ilmu Administrasi dan Kebijakan Publik, 2026)
This study aims to analyze school policies regarding character and religious education at SMA Muhammadiyah Mlati. Utilizing a qualitative research design with a case study approach, data were gathered through semi-structured interviews with key institutional stakeholders, passive participatory observations, and document analysis. Data trustworthiness was ensured via source and methodological triangulation, while data analysis applied the interactive model of Miles, Huberman, and Saldana. The results demonstrate that the school successfully established a holistic character education ecosystem through five core pillars: integrating Al-Islam and Kemuhammadiyahan (ISMUBA) values as the foundation, habituating collective practical worship, mandating Hizbul Wathan scouting, applying restorative-educational religious sanctions, and synergizing religious literacy with Tarjih cadreization via student-led Kultum programs. This study concludes that the synchronization of structural policies and daily practices successfully fosters students' moral autonomy and leadership competence. It is recommended that the school digitalizes its worship tracking systems to enhance parent-teacher collaboration.